Socio-Economic Development and its Axiological Aspects - Chojnicki, Zbyszko (Quaestiones Geographicae, 2010)
The article presents notions and issues concerning socio-economic development in an axiological perspective. Their presentation is limited to those the present author considers valid, and ignores their wider context as expounded in the various theories of socio-economic development. Underlying the axiological approach to socio-economic development is the opinion that the character of and research on socio-economic development are not neutral axiologically because values are an inherent component of human activity; they stimulate it and give it a direction. The knowledge concerning human activity makes use of evaluative concepts and judgements. The article discusses: (1) the concept of socio-economic development, (2) basic axiological notions, and (3) axiological problems of socio-economic development.